Management of Panfacial Trauma: Sequencing and Pitfalls - Massenburg, Benjamin B.; Lang, Melanie S. (Seminars in Plastic Surgery, 2021)
Panfacial trauma refers to high-energy mechanism injuries involving two or more areas of the craniofacial skeleton, the frontal bone, the midface, and the occlusal unit. These can be distracting injuries in an unstable patient and, as in any trauma, Advanced Trauma Life Support (ATLS) protocols should be followed. The airway should be secured, bleeding controlled, and sequential examinations should take place to avoid overlooking injuries. When indicated, neurosurgery and ophthalmology should be consulted as preservation of brain, vision, and hearing function should be prioritized. Once the patient is stabilized, reconstruction aims to reduce panfacial fractures, restore the horizontal and vertical facial buttresses, and resuspend the soft tissue to avoid the appearance of premature aging. Lost or comminuted bone can be replaced with bone grafts, although adequate reduction should be ensured prior to any grafting. Operative sequencing can be performed from top-down and outside-in or from bottom-up and inside-out depending on patient presentation. All protocols can successfully manage panfacial injuries, and the emphasis should be placed on a systematic approach that works from known areas to unknown areas.
Keywords: panfacial trauma; le fort fracture; facial fracture; bone graft; mandible fracture; frontal bone fracture